Atomic emission spectrometer "Grand" for studying the features of accumulation and distribution of chemical elements in objects of animal origin - Otmakhov, Vladimir I.; Sarkisov, Yuri S.; Obukhova, Anastasiy; Petrova, Elena V.; Gorlenko, Nikolay P. (XV International scientific conference "Interagromash 2022" : global precision Ag innovation 2022)
In this paper, the possibilities of using the arc atomic emission spectrometer “Grand” with multichannel emission spectrum analyzers (MAES) in terms of elemental analysis of objects of animal origin are expanded. Metrologically certified methods that have passed preliminary metrological examination were used for research. Of particular interest is the construction of periodic dependences of changes in certain parameters of the objects under study with an increase in the ordinal number of the element determining their structure and organization, as well as the construction on this foundation of predictions about the properties and behavior of living objects when interacting with each other. The features of the distribution of chemical elements as the charge of the atomic nucleus increases are reflected in the internal structure of the periodic system. In this regard, it is established in this work that the dependences of the accumulation and distribution of chemical elements in the studied living organisms with increasing ordinal number of the element in the periodic table of D. I. Mendeleev are also periodic.